Persepsi Kesiapan Kerja Mahasiswa Setelah Melaksanakan Pengenalan Lapangan Persekolahan (PIP) Pada Fakultas Keguruan dan Ilmu Pendidikan - Simatupang, Putri; Melly Novalia; Vitriani (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2024)
Student work readiness is a condition that must be prepared by students and universities before students complete their studies. So that after graduation they will work and can create their own jobs in a relatively short time. The lack of work readiness of students is due to the Introduction of the School Field has not been applied optimally due to the lack of skills and strong mentality when dealing with students, lack of personality as a prospective educator, and lack of opportunities to explore with the knowledge provided by field supervisors and lecturers. This study aims to examine and describe the work readiness of students after implementing the Introduction to the School Field (PLP). This research is a quantitative study with a population of 2019 Faculty of Teacher Training and Education students. The sampling technique used in this study was total sampling with 92 student respondents. The results of this study indicate that the work readiness of FETT students at Muhammadiyah Riau University is influenced by the Introduction of the School Field, this can be proven by the R - Square value of 0.638 (64%).